The sperm parameters and prediction of IUI success (Annals of Medical Research, 2021)
Aim: We aimed to compare the different sperm motility parameters in pregnant and non-pregnant patients who underwent IUI in our tertiary center. Material and Methods: Total of 110 gonadotrophin plus IUI patients were evaluated between 2017 January and January 2020 in this retrospective study. Some demographic features and infertility time, post-wash sperm parameters and basal hormone levels were compared between pregnant and non-pregnant patients and the regression analysis method was used to evaluate IUI success between other parameters.Results: Endometrial thickness (9.1±1.4 vs.7.6±1.4 ) on hCG triggering day and , post-wash progressive sperm motility value together with the a ratio and infertility time were correlated well with IUI success (ie pregnacy result ) between 38 pregnant and 72 non pregnant patients.Conclusion: After wash progressive sperm ratio may predict IUI success with infertility time and endometrial thickness.
Keywords: Intrauterine insemination; infertility; motile sperm